Sunnatullah as a Principle of Divine Order: A Philosophical Analysis and Its Relevance to the Development of Modern Islamic Education - Raharjo, Harmanto; Basri, Hasan; Sadiah, Dewi; Mulyadi, Mulyadi; Rahmi, Aulia (FOKUS Jurnal Kajian Keislaman dan Kemasyarakatan, 2025)
This study aims to analyze sunnatullah as a principle of divine order from a philosophical perspective and examine its relevance to the development of modern Islamic education. The research focuses on understanding the essence of sunnatullah, exploring the views of classical and contemporary Muslim scholars, and identifying its implications for shaping an educational paradigm that is adaptive to contemporary challenges. This research employs a qualitative method with a library research approach, involving an in-depth study of primary and secondary sources such as Qur’anic exegesis, classical Islamic scholarship, and relevant academic works. Data were analyzed using descriptive-analytical and philosophical-critical approaches to reveal the ontological, epistemological, and axiological dimensions of sunnatullah. The findings indicate that sunnatullah encompasses not only the immutable laws governing the universe but also social and historical laws that can be studied and applied. These findings affirm that the principle of divine order serves as a conceptual foundation for developing Islamic education that is integrative, rational, transformative, and responsive to modern challenges.